Специфіка використання твердосплавних різальних пластин з покриттям при чорновій та напівчистовій токарній обробці деталей важкого машинобудування - Мироненко, Є. В.; Калініченко, В. В.; Хорошайло, В.; Гузенко, Д. Є. (Національний технічний університет "Харківський політехнічний інститут", 2019)
У статті на основі результатів досліджень узагальнені специфічні особливості чорнової та напівчистової токарної обробки деталей важкого машинобудування різцями з твердосплавними різальними пластинами з покриттям. Обґрунтовано вибір марок твердих сплавів з покриттям, найбільш перспективних для використання при чорновій та напівчистовій токарній обробці сталевих деталей на важких верстатах.

In this article on the basis of research results specific features of roughing and semifinish turning of heavy machinery parts by cutting tools with coated hard-alloy cutting plates are generalized. The factors that have a negative impact on the durability of cutting tools, processing performance and energy efficiency of processing at the roughing and semifinish turning of steel parts on heavy lathes are listed. The results of production tests of cutting tools with coated hard-alloy cutting plates of the world's leading manufacturers at the roughing and semifinish turning of steel mill rolls with large roll barrel diameters are analyzed. On the basis of production tests results of cutting tools with cutting plates SCMT 380932 in coated hard alloys manufactured by Pramet, Korloy, Taegu Tec, Canela, Harditalia and other manufacturers at the longitudinal roughing of mill roll barrels in diameter range from 1120 mm to 1590 mm the best performance characteristics were demonstrated by cutting tools with cutting plates of hard alloy 6635 with MT-CVD coating manufactured by Pramet. On the basis of production tests results of cutting tools with cutting plates CNMG 190616 in coated hard alloys of different grades manufactured by Sandvik Coromant, Pramet, Stellram, Iscar, Toshiba Tungaloy, Mitsubishi at the longitudinal semifinish turning of mill rolls of alloy steels in diameter range of barrel from 521 mm to 1300 mm the best performance characteristics were demonstrated by cutting tools with cutting plates of hard alloys GC4005, GC4015, GC4225 manufactured by Sandvik Coromant and hard alloy 6610manufactured by Pramet. The choice of grades of hard alloys with coating which are most prospected for use in roughing and semifinish turning of steel parts on heavy lathes is ground. As recommended grades of hard alloys from researched area of turning of heavy machinery parts are offered hard alloys GC4005, GC4015, GC4025, GC4035, GC4225 manufactured by Sandvik Coromant and hard alloys 6610, 6635 manufactured by Pramet; the characteristics of these hard alloys, which determine the effectiveness of their use in the researched area of turning are presented.
Specifics of use of coated hard-alloy cutting plates in roughing and semifinish turning of heavy machinery parts
Keywords: викришування; працездатність; продуктивність обробки; енергоефективність; spalling; functional performance; processing performance; energy efficiency